Primary medical care continuity and patient mortality: a systematic review - Baker, Richard; Freeman, George K; Haggerty, Jeannie L; Bankart, M John; Nockels, Keith H (British journal of general practice, 2020)
A 2018 review into continuity of care with doctors in primary and secondary care concluded that mortality rates are lower with higher continuity of care. This association was studied further to elucidate its strength and how causative mechanisms may work, specifically in the field of primary medical care. Systematic review of studies published in English or French from database and source inception to July 2019. Original empirical quantitative studies of any design were included, from MEDLINE, Embase, PsycINFO, OpenGrey, and the library catalogue of the New York Academy of Medicine for unpublished studies. Selected studies included patients who were seen wholly or mostly in primary care settings, and quantifiable measures of continuity and mortality. Thirteen quantitative studies were identified that included either cross-sectional or retrospective cohorts with variable periods of follow-up. Twelve of these measured the effect on all-cause mortality; a statistically significant protective effect of greater care continuity was found in nine, absent in two, and in one effects ranged from increased to decreased mortality depending on the continuity measure. The remaining study found a protective association for coronary heart disease mortality. Improved clinical responsibility, physician knowledge, and patient trust were suggested as causative mechanisms, although these were not investigated. This review adds reduced mortality to the demonstrated benefits of there being better continuity in primary care for patients. Some patients may benefit more than others. Further studies should seek to elucidate mechanisms and those patients who are likely to benefit most. Despite mounting evidence of its broad benefit to patients, relationship continuity in primary care is in decline - decisive action is required from policymakers and practitioners to counter this.